Principles of scientific method: Notes on Lectures by Dr K.R. Popper given at the University of Otago, 22–26 May 1945; Lecture 2. Testing of theories - Popper, Karl (New Zealand Science Review, 2012)
​One puts up a hypothesis, a guess, a leap into the unknown, and from this one deduces consequences and then tests these.Mill thought that if these tests are to mean anything, they have to establish the hypothesis. But the fundamental procedure is the reverse – the test has to be an attempt to refute the hypothesis. One is, of course, happy if refutation is not done. We can call this view ‘falsificationism’, i.e. one adopts a hostile attitude to the hypothesis.